Investigating the impact of Internet of Things services from a smartphone app on grocery shopping. (January 2020) - Fagerstrøm, Asle; Eriksson, Niklas; Sigurdsson, Valdimar
Abstract: This study investigates the impact of Internet of Things (IoT) services from a smartphone app in a retail grocery shopping situation. It examines four variables, namely price, expiry date, quality indicators and offers. All four variables were examined in relation to two levels; traditional information and IoT services. A scenario was arranged whereby 226 participants were to purchase, among other products, fresh salmon in a grocery store using the store's smartphone app. Findings from a conjoint study show that the following IoT services; "updated expiry date", "aggregated national customer experience index", and "personalized offer based on product in the basket" evoked the approach and abated avoidance tendencies to explore the smartphone app, while simultaneously increasing the likelihood of buying based on information from the app. The IoT service "Real-time price" had a varied impact on participant approach-avoidance tendencies to interact with the app. Scenario simulation analysis shows that some IoT services can be a deal-breaker in a competitive grocery market. Consequently, analyzing the impact of IoT services through the lenses of approach-avoidance distinction and choice indication can help retail grocery managers develop more effective marketing strategies that deliver convenience to the consumers. Highlights: Consumers demand more convenience when shopping for groceries. This study investigates the impact of IoT services in the grocery choice situation. IoT services related to expiry date, quality and offer increase consumers' tendencies to use a smartphone app. IoT services from a smartphone app increased consumers' likelihood to buy. Some IoT services can be a deal-breaker in a competitive market.